PENGARUH MOTIVASI, DISIPLIN, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL STUDI PADA POLDA JAWA TENGAH - Yohanes Denny Kurnia Prasetyo, 11.05.51.0019 (Students Journal of Economic and Management, 2015)
This study analyzes the influence of Motivation, Discipline, and Work Environment on the performance of civil servants in the Central Java Police. The research object in this paper is POLDA CENTRAL JAVA. The sampling technique in this research is to use the Simple Random Sampling amounted to 80 respondents. Analysis of the data used include test the validity of the product moment, coefficient alpha reliability test (Alpha Cronbrach), multiple regression analysis, t test to test and prove the research hypothesis. The results of the research are: (1). Motivation positive and significant impact on the performance of employee, the more often the motivation is given it will improve the performance of employees (2) Discipline and no significant positive effect on the performance of employees, the training level of discipline given employee will be increased. (3) Working Environment and significant positive effect on employee performance, the better the work environment is given then the employees would feel comfortable Keywords:Motivation, Discipline, Work Environment and Employee Performance